Analysis and Evaluation of WBG Power Device in High Frequency Induction Heating Application - Kwang-Hyung Cha; Chang-Tae Ju; Rae-Young Kim (Energies, 2020)
A device suitability analysis is performed herein by comparing the performance of a silicon carbide (SiC) metal-oxide-semiconductor-field-effect transistor (MOSFET) and a gallium nitride (GaN) high-electron mobility transistor (HEMT), which are wide-bandgap (WBG) power semiconductor devices in induction heating (IH) systems. The WBG device presents advantages such as high-speed switching owing to its excellent physical properties, and when it is applied to the IH system, a high output power can be achieved through high-frequency driving. To exploit these advantages effectively, a suitability analysis comparing SiC and GaN with IH systems is required. In this study, SiC MOSFET and GaN HEMT are applied to the general half-bridge series resonant converter topology, and comparisons of the conduction loss, switching loss, reverse conduction loss, and thermal performance considering the characteristics of the device and the system conditions are performed. Accordingly, the device suitability in an IH system is analyzed. To verify the device conformance analysis, a resonant converter prototype with SiC and GaN rated at 650 V is constructed. The analysis is verified by an experimental comparison of power loss and thermal performance.